Dual Ribosome Profiling reveals metabolic limitations of cancer and stromal cells in the tumor microenvironment - Avilés Huerta, Daniela; Del Pizzo, Rossella; Kowar, Alexander; Baig, Ali Hyder; Palazzo, Giuliana; Stepanova, Ekaterina; Amaya Ramirez, Cinthia Claudia; D'Agostino, Sara; Ratto, Edoardo; Pechincha, Catarina; Siefert, Nora; Engel, Helena; et al. (Nature Communications, 2025)
The tumor microenvironment (TME) influences cancer cell metabolism and survival. However, how immune and stromal cells respond to metabolic stress in vivo, and how nutrient limitations affect therapy, remains poorly understood. Here, we introduce Dual Ribosome Profiling (DualRP) to simultaneously monitor translation and ribosome stalling in multiple tumor cell populations. DualRP reveals that cancer-fibroblast interactions trigger an inflammatory program that reduces amino acid shortages during glucose starvation. In immunocompetent mice, we show that serine and glycine are essential for optimal T cell function and that their deficiency impairs T cell fitness. Importantly, immune checkpoint blockade therapy imposes amino acid restrictions specifically in T cells, demonstrating that therapies create distinct metabolic demands across TME cell types. By mapping codon-resolved ribosome stalling in a cell‑type‑specific manner, DualRP uncovers metabolic crosstalk that shapes translational programs. DualRP thus offers a powerful, innovative approach for dissecting tumor cell metabolic interplay and guiding combined metabolic-immunotherapeutic strategies.
Gesehen am 22.10.2025